1956
DOI: 10.1128/jb.71.2.140-148.1956
|View full text |Cite
|
Sign up to set email alerts
|

Differential Reversal of Inhibitory Effects of Folic Acid Analogues on Growth, Division, and Deoxyribonucleic Acid Synthesis of Microorganisms

Abstract: 3 The following abbreviations are used in this paper: RNA (ribonucleic acid), DNA (deoxyribonucleic acid), PGA or FA (pteroylglutamic acid = folic acid), CoF (coenzyme form of folic acid), AM or 4-amino PGA (aminopterin), and AAF (aminoan-fol = 4-aminopteroylaspartic acid).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1956
1956
2009
2009

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…In a 2 per cent peptone-water medium, for example, the bacteriostatic activities of aminopterin and aminoan-fol against E. coli were only 25 per cent of those in the defined medium. In the paper by Webb and Nickerson (1956), certain amino acids are shown partially to overcome the inhibitory effects of the antagonists.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 2 per cent peptone-water medium, for example, the bacteriostatic activities of aminopterin and aminoan-fol against E. coli were only 25 per cent of those in the defined medium. In the paper by Webb and Nickerson (1956), certain amino acids are shown partially to overcome the inhibitory effects of the antagonists.…”
Section: Methodsmentioning
confidence: 99%
“…This was in contrast to cells harvested from control cultures of the same age, in which the nuclear elements were readily demonstrated after appropriate hydrolysis. It is possible that the failure to obtain convincing recordls of the nuclear structures of the filamentous cells bv (lirect methods may be of somie significance with regard to the mo(le of action of the folic acid analogues (Webb and Nickerson, 1956 necessary to transfer a thick suspension of the cells to the surface of a nutrient agar plate maintained at 37 C. After 30 to 90 min (before multiplication occurred) impression preparations were made from blocks of the agar cut from the plate and fixed in osmium tetroxide vapor. The "young" filamentous cells obtained by this technique then appeared to possess nuclear elements regularly spaced along their length.…”
Section: ]mentioning
confidence: 99%
“…Most cell-division studies have concentrated on nucleic acid synthesis, particularly the pyrimidine, thymine, and several studies reported involvement of vitamin B12 and folic acid in cell division (Deibel et al, 1956;Webb and Nickerson, 1956;Nickerson and Webb, 1956;Jeener and Jeener, 1952). Thymine, vitamin B12, and folic acid are all involved in C1 metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Tetrahydrofolate is converted into one-carbon tetrahydrofolate derivatives such as 10-formyl tetrahydrofolate, 5,10-methenyl tetrahydrofolate and 5,10-methylene tetrahydrofolate, which are used as one-carbon donors for the biosynthesis of purines and pyrimidines (dUMP), for the interconversion of glycine and serine but also for the synthesis of formylated methionyl-tRNA. dependent metabolites from the growth medium leads to a higher susceptibility toward methotrexate (Webb & Nickerson, 1956;Harvey, 1973). We have tested folate production on a medium with and without folate-dependent metabolites for the control strain and the folate-overproducing strain ( Table 1).…”
Section: Folate Overproduction As a Mechanism For Methotrexate Resistmentioning
confidence: 99%